Effect of combined use of mustard oilcake, ammonium sulphate, and superphosphate on fish and aquatic ecosystem - Sarkar, S K (Indian Journal of Fisheries, 2011)
There are a few investigations in India onthe influence of different chemical fertilizersand organic manures on commercially importantfish and aquatic ecosystem. The use offertilizers in fish ponds is on increase. However,their liberal application causes drasticdecline in the abundance offish and their foodorganisms due to toxic action of nitrogen fertilizersand their metabolites